Artificial Intelligence and Criminal Liability: New Challenges for Indonesian Criminal Law - Ade Ari Gumilar; Zabidin; Rica Gusmarani; Makkah; Iwan Rasiwan (Universitas Muhammadiyah Palu, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed various aspects of human life, including the field of criminal law. AI technology is no longer limited to functioning as a supporting tool; it is increasingly capable of operating in a semi-autonomous or fully autonomous manner through machine learning systems. This development raises new legal challenges, particularly concerning criminal liability when AI systems are involved in actions that constitute criminal offenses. The primary issue lies in determining the appropriate legal subject to be held accountable, given that the Indonesian criminal law system remains predominantly centered on human actors (natural persons). This study aims to examine the challenges of criminal liability arising from the use of AI in Indonesia and to explore relevant legal concepts that may address these emerging issues. The research employs a normative juridical method, utilizing both statutory and conceptual approaches. The legal materials analyzed include legislation, scholarly publications, and prior studies related to AI and criminal law. The findings indicate that AI has not yet been recognized as a legal subject within the Indonesian legal framework, and therefore cannot be held criminally liable. As a result, liability is still attributed to human actors, including developers, users, and corporations that deploy AI technologies. Nevertheless, the increasing autonomy of AI systems calls for a re-evaluation and adaptation of existing criminal law doctrines to ensure legal certainty, fairness, and adequate protection for society in the digital era.